Children’s Health and Asset Endowments in Cameroon - Mbu Daniel Tambi; Peter Arung Etta (Indonesian Journal of Economics and Management, 2022)
This study attempts to carry out a comprehensive analysis on “children’s health and asset endowments (AE) in Cameroon”. The objective is to examine the effects of child health on household asset endowments. From the Control Function Model, we compute the result using the combined 2004/2011 demographic and health survey. The result of the Control function shows that child health is positively and significantly associated with the production of HAE. In addition, the relationship between child health and asset indicator is a matter of the male gender while decomposing child health effect on AE for household residence, we realized that it is more an issue of rural household residence due to inadequate provision of public goods. In terms of policy, child health should be included in the new vision of successful asset building so that, families raising children with good health, asset accumulation should start early and last long.